2001
DOI: 10.1038/sj.bjp.0704303
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation and the activation of proteinase‐activated receptor 2 (PAR2) by human mast cell tryptase

Abstract: 1 Human mast cell tryptase appears to display considerable variation in activating proteinaseactivated receptor 2 (PAR 2 ). We found tryptase to be an ine cient activator of wild-type rat-PAR 2 (wt-rPAR 2 ) and therefore decided to explore the factors that may in¯uence tryptase activation of PAR 2 . 2 Using a 20 mer peptide (P20) corresponding to the cleavage/activation sequence of wt-rPAR 2 , tryptase was as e cient as trypsin in releasing the receptor-activating sequence (SLIGRL...). However, in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
3
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 43 publications
3
119
3
2
Order By: Relevance
“…Cell Culture. Previously described Kirsten virus-transformed rat kidney cells (KNRK; American Type Culture Collection, Manassas, VA) permanently vector-transfected with rat PAR 2 (KNRK-PAR 2 ) were grown to 90% confluence with antibioticcontaining 10% FBS growth medium (Invitrogen), supplemented with 0.6 mg͞ml geneticin to maintain vector-selective pressure (13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Culture. Previously described Kirsten virus-transformed rat kidney cells (KNRK; American Type Culture Collection, Manassas, VA) permanently vector-transfected with rat PAR 2 (KNRK-PAR 2 ) were grown to 90% confluence with antibioticcontaining 10% FBS growth medium (Invitrogen), supplemented with 0.6 mg͞ml geneticin to maintain vector-selective pressure (13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure used was similar to that described in ref. 13. Trypsin (25 ng), granzyme A (450 ng), and C. rodentium-or sham-infected luminal fluid (3 l) was incubated with P20 peptide (200 M), which corresponds to the cleavage͞activation site of the wtrPAR 2 N terminus [ 30 GPNSKGR2SLIGRLDT 45 P-YGGC (2, trypsin cleavage site, -YGGC was added for affinity column coupling for another project)] in 50 mM Hepes͞150 mM NaCl, pH 7.5 (75 l).…”
Section: Cleavage Of a 20-mer Peptide (P20) Corresponding To The Cleamentioning
confidence: 99%
“…The explanation of this discrepancy is unknown. However, alterations in the extent of receptor glycosylation dramatically affect the ability of tryptase to cleave and activate PAR2 (28). Thus, deglycosylation in vivo could regulate tryptase activation of PAR2.…”
Section: Tryptase and Trypsin May Activate Par2 In The Inflamed Airwaymentioning
confidence: 99%
“…In addition, the alanine mutations were created at amino acid positions Phe 55 -Trp 56 or Val 72 -Ser 73 of N62Q/ N75Q to generate cathepsin G mutant (F55A/W56A) or proteinase 3 mutant (V72A/S73A). KNRK and CHO cells permanently expressing wild-type or mutant hPAR 1 cell lines were generated and cultured as described previously (Table 1) (19,20).…”
Section: Generation Of Glycosylation-deficient Mutant Cellmentioning
confidence: 99%
“…Our previous pharmacological studies have reported that activation of hPAR 2 by mast cell tryptase can be regulated by receptor N-terminal glycosylation (19,20). To our knowledge, hPAR 1 contains a total of five predicted sites for N-linked glycosylation; three sequons are located on the receptor N terminus (Asn 35 -Ala 36 -Thr 37 , Asn 62 -Glu 63 -Ser 64 , and Asn 75 -Lys 76 -Ser 77 ), and two are located within extracellular loop 2 (ECL2; Asn 250 -Ile 251 -Thr 254 , and Asn 259 -Glu 260 -Thr 261 ) ( Fig.…”
mentioning
confidence: 99%